General practice reformative agenda 2024 (protocol) - Shrestha, Ashis; Ghimire, Rajan; Bajracharya, Sumana; Bom, Rabin; Samal, Anup; Joshi, Arabind; Dangal, Binod; Maharjan, Kripa; Raj Bhandari, Bibek; Kharal, Pushpa Mani; Dawadi, Bishwa; Shah, Arati; et al. (Journal of General Practice and Emergency Medicine of Nepal, 2023)
The healthcare system undergoes frequent reforms, including various services. General practice (GP), a longstanding specialty in Nepal, now requires further changes, due to changing and growing needs of the country. To facilitate this, it’s essential to identify key areas for reform supported by evidence. To gather evidence, we’ve designed a qualitative study based on grounded theory. The researcher aims to engage with a large number of GPs using virtual methods. Participants will be contacted through focused group discussions, key-person interviews, polls, and debates. In the first round, key issues will be identified, and in the second round, potential solutions will be explored. Our goal is that these findings will assist stakeholders in pinpointing gaps in policies, educational strategies, research, and the overall development of GPs. With the implementation of these findings, we anticipate a well-defined role for GPs within the national health system.